2023
DOI: 10.1590/1809-4392202201541
|View full text |Cite
|
Sign up to set email alerts
|

New records of Geastrum (Geastrales, Basidiomycota) for the Amazon

Abstract: Fungi of the genus Geastrum are known as earthstar fungi, due to the stelliform morphology of their basidiomes. In the Amazon domain, there are 25 catalogued species of Geastrum, with several new records in recent years. Here we report three new species records of Geastrum for the Brazilian Amazon. Geastrum calycicoriaceum and G. rubropusillum were recorded in the southwestern transition zone between Amazon forest and Cerrado savanna. Geastrum calycicoriaceum was recorded for the first time in Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…A portion of the basidiomycetes corresponds to gasteroid fungi, widely distributed in the tropics (Mueller et al, 2007), mainly in Brazil, where the diversity of the group increases every year (Accioly et al, 2019;Assis et al, 2022;Ferreira-Sá et al, 2021;Freitas et al, 2023;Santana & Couceiro, 2023). Studies with this group revealed the production of important substances with proven biological activity (Liu & Zhang, 2004;Dore et al, 2007;Coetze and Van Wyk, 2009), but there is a study gap regarding the discoloration of synthetic dyes.…”
Section: Trypan Blue Dye Discoloration In Solid Culture Mediummentioning
confidence: 99%
“…A portion of the basidiomycetes corresponds to gasteroid fungi, widely distributed in the tropics (Mueller et al, 2007), mainly in Brazil, where the diversity of the group increases every year (Accioly et al, 2019;Assis et al, 2022;Ferreira-Sá et al, 2021;Freitas et al, 2023;Santana & Couceiro, 2023). Studies with this group revealed the production of important substances with proven biological activity (Liu & Zhang, 2004;Dore et al, 2007;Coetze and Van Wyk, 2009), but there is a study gap regarding the discoloration of synthetic dyes.…”
Section: Trypan Blue Dye Discoloration In Solid Culture Mediummentioning
confidence: 99%